1985
DOI: 10.1093/nar/13.22.7929
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the rate of metallothionein mRNA POLY(A)-shortening using RNA blot hybridization

Abstract: A progressive reduction in the size of rat metallothionein-l mRNA following induction by copper chloride or dexamethasone was demonstrated on RNA blots, and was shown to be due to shortening of the poly(A)-tail. The rate of poly(A) removal was the same in rat liver and kidney following copper chloride induction, in rat liver following dexamethasone induction, and in mouse liver following copper chloride induction. In mouse liver metallothionein-l and 2 mRNAs were shortened at the same rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…In the preceding analysis, nuclear b-globin mRNA had a migration on gel identical with that of the cytoplasmic one, suggesting that it was fully processed mRNA (both spliced and polyadenylated)+ The metabolism of the poly(A) tail was further investigated in a reinduction experiment designed to roughly synchronize the transcripts+ Indeed, it has been previously reported that if limiting doses of tetracycline are used, a reinduction from the tet-off promoter/regulator system could be observed within 2 h after washing off the tetracycline from the culture medium (Xu et al+, 1998)+ tTA-b-glo cells were grown for 3 days in the presence of 80 ng/mL of tetracycline, a concentration just sufficient to achieve maximal inhibition of transcription+ Cells were then extensively washed and further incubated in the absence of tetracycline+ A Northern blot analysis of the nuclear and cytoplasmic RNA prepared at different time postwashing is presented Fig+ 7A+ Resumption of b-globin mRNA accumulation could be detected from 2 h on+ Importantly, in the nucleus, the newly synthesized transcripts appeared to migrate more slowly than most of the transcripts present in unrepressed cells (Fig+ 7A, lane C), suggesting that they have a longer poly(A) tail+ To confirm this, the 3 h, 6 h, and unrepressed samples were submitted to poly(A) tail digestion using oligodT/ RNase H treatment (Fig+ 7B)+ After poly(A) tail removal, the nuclear and cytoplasmic b-globin mRNAs had the expected migration for the 713-nt fully spliced transcripts according to the molecular weight markers (Fig+ 7B, lane MW) (note that introns 1 and 2 are 126 and 573 nt long, respectively)+ Furthermore, the shift in mobility due to the poly(A) tail digestion indicated that at 3 h postwashing, the b-globin mRNAs had a poly(A) tail of about 200 nt, which ranged from 150 to 200 nt at 6 h and from 30 to 200 nt in unrepressed cells (see Fig+ 7B, bottom panel, for an intensity adjusted picture)+ Thus, as expected, newly synthesized transcripts had a long poly(A) tail that slowly decreased over time, in agreement with the deadenylation rate of 20 nt/h that has been observed for other mRNAs (Mercer & Wake, 1985)+ More importantly, this deadenylation was observed not only in the cytoplasmic compartment, but also in the nuclear compartment+ Is there a relation between transcription and mRNA export rates?…”
Section: Characterization Of the Poly(a) Tail Of B-globin Nuclear Mrnasupporting
confidence: 81%
“…In the preceding analysis, nuclear b-globin mRNA had a migration on gel identical with that of the cytoplasmic one, suggesting that it was fully processed mRNA (both spliced and polyadenylated)+ The metabolism of the poly(A) tail was further investigated in a reinduction experiment designed to roughly synchronize the transcripts+ Indeed, it has been previously reported that if limiting doses of tetracycline are used, a reinduction from the tet-off promoter/regulator system could be observed within 2 h after washing off the tetracycline from the culture medium (Xu et al+, 1998)+ tTA-b-glo cells were grown for 3 days in the presence of 80 ng/mL of tetracycline, a concentration just sufficient to achieve maximal inhibition of transcription+ Cells were then extensively washed and further incubated in the absence of tetracycline+ A Northern blot analysis of the nuclear and cytoplasmic RNA prepared at different time postwashing is presented Fig+ 7A+ Resumption of b-globin mRNA accumulation could be detected from 2 h on+ Importantly, in the nucleus, the newly synthesized transcripts appeared to migrate more slowly than most of the transcripts present in unrepressed cells (Fig+ 7A, lane C), suggesting that they have a longer poly(A) tail+ To confirm this, the 3 h, 6 h, and unrepressed samples were submitted to poly(A) tail digestion using oligodT/ RNase H treatment (Fig+ 7B)+ After poly(A) tail removal, the nuclear and cytoplasmic b-globin mRNAs had the expected migration for the 713-nt fully spliced transcripts according to the molecular weight markers (Fig+ 7B, lane MW) (note that introns 1 and 2 are 126 and 573 nt long, respectively)+ Furthermore, the shift in mobility due to the poly(A) tail digestion indicated that at 3 h postwashing, the b-globin mRNAs had a poly(A) tail of about 200 nt, which ranged from 150 to 200 nt at 6 h and from 30 to 200 nt in unrepressed cells (see Fig+ 7B, bottom panel, for an intensity adjusted picture)+ Thus, as expected, newly synthesized transcripts had a long poly(A) tail that slowly decreased over time, in agreement with the deadenylation rate of 20 nt/h that has been observed for other mRNAs (Mercer & Wake, 1985)+ More importantly, this deadenylation was observed not only in the cytoplasmic compartment, but also in the nuclear compartment+ Is there a relation between transcription and mRNA export rates?…”
Section: Characterization Of the Poly(a) Tail Of B-globin Nuclear Mrnasupporting
confidence: 81%
“…The effect of TTP expression in causing shortening of the TNF-␣ mRNA suggested that TTP was promoting deadenylation of the TNF-␣ mRNA poly(A) tail. To evaluate this possibility, oligo(dT) [12][13][14][15][16][17][18] (P1) was added to total cellular RNA, and RNase H was used to remove the poly(A) tail (31). When this technique was used on RNA samples from cells cotransfected with CMV.mTNF-␣ and either vector alone or TTP expression constructs (H6E.HGH3Ј in Fig.…”
Section: Figmentioning
confidence: 99%
“…Moreover, in a number of studies, changes in the size distribution of poly(A) tails are correlated with alterations in mRNA decay rates (for review, see Bemstein and Ross 1989;Peltz et al 1991). In addition, for several mRNAs, a portion (-25 or more adenylate residues) of the poly(A) tail persists after shortening of the majority of the poly(A) tail has occurred, indicating that there are at least two phases of deadenylation in eukaryotes other than yeast (Mercer and Wake 1985;Restifo and Guild 1986;Kleene 1989;Shyu et al 1991). Given the fundamental similarity of other physiological processes between yeast and more complex eukaryotes (e.g., Lee and Nurse 1987;Shuster and Guthrie 1990), we speculate that additional steps in this yeast decay pathway may occur in an analogous manner in complex eukaryotes.…”
Section: Deadenylation-dependent Decay In Other Eukaryotesmentioning
confidence: 99%